Plan de ordenamiento turístico para el desarrollo de la parroquia rural Canuto del Cantón Chone - Bravo Triviño, Evelyn Valentina (2023)
for the development of the Canuto parish in the Chone canton, applying documentary/bibliographical and field research with a mixed non-experimental exploratory approach based on analytical-synthetic and descriptive methods, which allowed to know the reality of the area under study and the incidence that it has; This design was structured in four phases: where in the first phase a characterization and multidimensional analysis of the territory was carried out using matrices and mapping of actors, in turn 196 surveys were applied to the population of the parish, which function to know the perception regarding tourism, obtaining that 76% of those surveyed are interested in tourism. In the second phase, the main products with territorial identity were identified in addition to the tourist sites in the area in order to measure the tourist potential of the territory; Subsequently, in the third phase, the problems and potentialities of the parish were analyzed through a strategic SWOT analysis, matrices (EFI, EFE, internal and external). Finally, a PDOT is established with a structure that allows the planning, management and tourist coordination of the territory with a vision of potentiating and marketing tourist products with territorial identity. It will be determined that Canuto has limitations in local development due to the lack of support in the planning of strategies by the GAD.